2011
DOI: 10.1080/10683160903113681
|View full text |Cite
|
Sign up to set email alerts
|

Assessing socially desirable responding and its impact on self-report measures among sexual offenders

Abstract: It is often assumed that offenders employ socially desirable responding when completing self-report questionnaires, thereby invalidating such measures. The aim of this study is to examine the extent that sexual offenders employ socially desirable responding and the impact that socially desirable responding, as measured by the Balanced Inventory of Desirable Responding-6 (BIDR: 6, Paulhus, Journal of Personality and Social Psychology, 46, 598Á609, 1984), has on self-report measures. The sample comprised 1730 ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 47 publications
(80 reference statements)
1
28
1
Order By: Relevance
“…Mills & Kroner, 2005. Therefore, the impact of socially desirable responding appeared to be minimal, consistent with Mathie and Wakeling's (2011) finding that socially desirable responding in sexual offenders is less than expected and has a limited influence on self-report methodologies.…”
Section: Socially Desirable Respondingsupporting
confidence: 87%
“…Mills & Kroner, 2005. Therefore, the impact of socially desirable responding appeared to be minimal, consistent with Mathie and Wakeling's (2011) finding that socially desirable responding in sexual offenders is less than expected and has a limited influence on self-report methodologies.…”
Section: Socially Desirable Respondingsupporting
confidence: 87%
“…According to this view, SDR may be correlated with Theory and Application of Dynamic Risk -24 dynamic risk factors (indeed, SDR was negatively correlated with dynamic risk in Mills and Kroner (2006) and Stevens et al (2015); see also Mathie and Wakeling (2010), but is not related to recidivism risk directly). This view is consistent with a recent reinterpretation of SDR by Uziel (2010), who suggested that instead of response bias, measures of SDR should be regarded as 'interpersonally oriented self-control', that is, SDR reflects the individual's ability to adjust to social situations and seek approval from others.…”
Section: Threats To Validity Of Dynamic Risk Measures: Socially Desirmentioning
confidence: 99%
“…Furthermore, the psychometric properties of the most SUBTYPES OF CHILD SEXUAL ABUSERS 6 commonly applied measures are problematic (Kalmus & Beech, 2005). Direct assessment procedures based on self-report suffer from their inherent transparency -probably less due to trait social desirability (Mathie & Wakeling, 2011;Tan & Grace, 2008) than to the legal implications of assessment in forensic contexts, and anxiety about socially ostracizing reactions of important others that are incompatible with offenders' personal aims (Maruna & Mann, 2006). Penile plethysmography (PPG) is an established -however still rather transparent -indirect measurement approach that is well validated (Seto, 2008), but expensive and labor intensive as a method in everyday routine practice.…”
Section: Assessing (Deviant) Sexual Interestmentioning
confidence: 99%